Climatic changes and the increase of modern pumping of irrigation in the southeastern oases of Morocco (Ferkla Oasis as a model). (Libya Journal of Geographical Studies, 2023)
Morocco is generally exposed, due to its geographical location and its climatic and hydrological characteristics, to water poverty, which is supported by the decline in the average annual per capita share of available water. The problem of water scarcity is acute in many dry and semi-arid areas, such as the oasis of Ferkla in the Grace Basin in the southeast, where scarcity in these areas over centuries imposed the acquisition by the populations of an austere management. The increase of human pressure as well as climate change severity concerning oases areas in recent decades have threatened the fragile balances obtained throughout centuries which has given rise to new ways of exploiting area and resources, including the emergence of modern water pumping as an attempt to adapt to the harsh climate.
Keywords: Modern pumping; Water resource; Oases; Ferkla; oasis; Water scarcity; Adaptation